Quem irá vigiar os próprios vigilantes?: a aplicação do estado de coisas inconstitucional ao poder judiciário e a cultura do encarceramento sob a ótica do realismo cardoziano - Pessoa, Jéssika Saraiva de Araújo (2020)
The object of study of this dissertation is the application of the Unconstitutional State of Things to the Judiciary, through a critical analysis of the Culture of Incarceration and its influence on judicial decisions. The objective of this research is to observe how the Culture of Incarceration influences judicial decisions and whether, based on the acting or omission by the Judiciary, we can apply the Unconstitutional State of Things institute to it, to the extent that a part of the provisional prisoners does not have decisions at first instance. The problem studied in this research is: Given the culture of incarceration and the IFOPEN/CNJ data on the prison system, can we apply the Unconstitutional State Institute of Things to the judiciary? The perspective adopted in this study is that of Benjamin Nathan Cardozo's American Realism and this research has a descriptive character, that is, to analyze reality as it is without the intention of proposing a new judicial model. Concerning the methodology used in this work, we used the deductive approach method and opted for the monographic procedure, the methodological objective adopted was exploratory and the research technique performed was a case study through bibliographical and documentary review. The hypothesis defended here is that the Unconstitutional State of Things can be applied to the judiciary since 40% of the provisional prison population do not have decisions in the first instance and their decisions are influenced by the culture of incarceration and contribute to the configuration of the “Dantesque” reality of Brazilian prisons.